2019
DOI: 10.1155/2019/1649423
|View full text |Cite
|
Sign up to set email alerts
|

A 6-Gene Risk Signature Predicts Survival of Glioblastoma Multiforme

Abstract: Background. This study aims to develop novel signatures for glioblastoma multiforme (GBM). Methods. GBM expression profiles from The Cancer Genome Atlas (TCGA) were downloaded and DEGs between tumor and normal samples were identified by differential expression analysis (DEA). A risk signature was developed by applying weighted gene coexpression network analysis (WGCNA) and Cox regression analysis. Patients were divided into high and low risk group, followed by evaluating the performance of the signature via Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
15
1
Order By: Relevance
“…Recently, five gene‐related signatures have been reported to predict the prognosis of patients with GBM. Therefore, we compared the prognostic value of our two‐gene (GRIA2 and RYR3) signature (hereinafter referred to as GR‐Sig) with that of different gene sets for predicting prognosis of patients with GBM: the 4‐gene (HOXC10, OSMR, SCARA3, and SLC39A10) signature derived from Cao's study 24 (hereinafter referred to as HOSS‐Sig); the 4‐gene (LHX2, MEOX2, SNAI2, and ZNF22) signature derived from Cheng's study 25 (hereinafter referred to as LMSZ‐Sig); the 5‐gene (PTPRN, RGS14, G6PC3, IGFBP2, and TIMP4) signature derived from Yin's study 26 (hereinafter referred to as PRGIT‐Sig); the 5‐gene (DES, RANBP17, CLEC5A, HOXC11, and POSTN) signature derived from Wang's study 27 (hereinafter referred to as DRCHP‐Sig); the 6‐gene (BPIFB2, HOXA13, LRRC10, NELL1, SDR16C5, and XIRP2) signature derived from Zhao's study 28 (hereinafter referred to as BHLNSX‐Sig).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, five gene‐related signatures have been reported to predict the prognosis of patients with GBM. Therefore, we compared the prognostic value of our two‐gene (GRIA2 and RYR3) signature (hereinafter referred to as GR‐Sig) with that of different gene sets for predicting prognosis of patients with GBM: the 4‐gene (HOXC10, OSMR, SCARA3, and SLC39A10) signature derived from Cao's study 24 (hereinafter referred to as HOSS‐Sig); the 4‐gene (LHX2, MEOX2, SNAI2, and ZNF22) signature derived from Cheng's study 25 (hereinafter referred to as LMSZ‐Sig); the 5‐gene (PTPRN, RGS14, G6PC3, IGFBP2, and TIMP4) signature derived from Yin's study 26 (hereinafter referred to as PRGIT‐Sig); the 5‐gene (DES, RANBP17, CLEC5A, HOXC11, and POSTN) signature derived from Wang's study 27 (hereinafter referred to as DRCHP‐Sig); the 6‐gene (BPIFB2, HOXA13, LRRC10, NELL1, SDR16C5, and XIRP2) signature derived from Zhao's study 28 (hereinafter referred to as BHLNSX‐Sig).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, omics technology and bioinformatics analysis have created an opportunity to identify novel molecular biomarkers and understand potential mechanisms in many tumors. For example, Zhao et al ( 12 ) identified a six-gene risk signature for the outcome prediction of GBM. Several studies have reported immune-related gene pairs (IRGPs) signature in ovarian cancer ( 13 ), liver cancer ( 14 ), and colorectal cancer ( 15 ) and showed well-predictive accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous genes have been validated to participate in the pathogenesis of GBM, and they serve as markers for differentiation and prognosis of GBM [ 3 , 4 ]. For example, overexpression of epidermal growth factor receptor (EGFR) is found in more than 30% of patients with GBM [ 5 ]. GBM tumor cells with EGFR have higher ability of migration and infiltration [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, overexpression of epidermal growth factor receptor (EGFR) is found in more than 30% of patients with GBM [ 5 ]. GBM tumor cells with EGFR have higher ability of migration and infiltration [ 5 ]. And patients with EGFR have a relatively reduced response to therapies, with shorter duration of survival [ 6 ].…”
Section: Introductionmentioning
confidence: 99%